2018
DOI: 10.1016/j.ygcen.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Acute salinity tolerance and the control of two prolactins and their receptors in the Nile tilapia (Oreochromis niloticus) and Mozambique tilapia (O. mossambicus): A comparative study

Abstract: Osmoregulation in vertebrates is largely controlled by the neuroendocrine system. Prolactin (PRL) is critical for the survival of euryhaline teleosts in fresh water by promoting ion retention. In the euryhaline Mozambique tilapia (Oreochromis mossambicus), pituitary PRL cells release two PRL isoforms, PRL and PRL, in response to a fall in extracellular osmolality. Both PRLs function via two PRL receptors (PRLRs) denoted PRLR1 and PRLR2. We conducted a comparative study using the Nile tilapia (O. niloticus), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…In the present study, levels of PRLR mRNA relative to BA mRNA (PRLR/BA) in pituitary gland of C. zilli were significantly higher in fish kept in fresh water (FW) than in those in saline water (SW). This is consistent with the change in PRLR mRNA in the pituitary gland following transfer of Nile tilapia to blackish water (20‰), as measured by Northern-blot analysis (Sandra et al, 1995, Yamaguchi et al, 2018. The expression of PRLR mRNA in the pituitary gland seems to be upregulated by the higher levels of circulating PRLs present in FW than in SW or in blackish water (Ayson et al, 1993;Auperin et al, 1994).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, levels of PRLR mRNA relative to BA mRNA (PRLR/BA) in pituitary gland of C. zilli were significantly higher in fish kept in fresh water (FW) than in those in saline water (SW). This is consistent with the change in PRLR mRNA in the pituitary gland following transfer of Nile tilapia to blackish water (20‰), as measured by Northern-blot analysis (Sandra et al, 1995, Yamaguchi et al, 2018. The expression of PRLR mRNA in the pituitary gland seems to be upregulated by the higher levels of circulating PRLs present in FW than in SW or in blackish water (Ayson et al, 1993;Auperin et al, 1994).…”
Section: Discussionsupporting
confidence: 80%
“…Zhu et al found that the NKAα1 mRNA expression levels in the gills of tilapia reached peak level at 24 h after transfer from freshwater to seawater [45]. Yoko et al research showed that PRLR2 facilitates acclimation responses to increased extracellular osmolality [46]. Yuan et al observed the synchronous expression trend of the renal PRLR with pituitary PRL (5d) and the asynchronous expression peaks between branchial (8d) and renal PRLR (5d) in olive flounder Paralichthys olivaceus, and the mRNA levels of PRL receptor (PRLR) in both gill and kidney displayed a similar trend to the pituitary PRL [47].…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin (PRL) and its receptor (PRLR) are critical for the survival of euryhaline teleost involving in ion uptake (Juan et al, 2002;Yamaguchi et al, 2017). Besides, cortisol plays a very important role in stress adaptation involving in immune, metabolism and other biological process (Szisch, Papandroulakis, Fanouraki, & Pavlidis, 2005), and its intracellular receptors glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) exert their corresponding biological processes after binding with serum cortisol (Prunet, Sturm, & Milla, 2006).…”
mentioning
confidence: 99%
“…Osmoregulation has been studied in many euryhaline teleosts, such as black porgy Acanthopagrus schlegeli (Tomy et al, 2009), golden pompano trachinotus ovatus (Ma et al, 2016), black-chinned tilapia (Sarotherodon melanotheron) (Tine, Guinand, & Durand, 2012) and salmonids (Flores & Shrimpton, 2012;McCormick, Regish, & Christensen, 2009). Prolactin (PRL) and its receptor (PRLR) are critical for the survival of euryhaline teleost involving in ion uptake (Juan et al, 2002;Yamaguchi et al, 2017). Besides, cortisol plays a very important role in stress adaptation involving in immune, metabolism and other biological process (Szisch, Papandroulakis, Fanouraki, & Pavlidis, 2005), and its intracellular receptors glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) exert their corresponding biological processes after binding with serum cortisol (Prunet, Sturm, & Milla, 2006).…”
mentioning
confidence: 99%